(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to measure the emotional freedom of kindergartens department students & know the differences between three stages ( first –second – third ) , to verify the aims of the research the researcher used a sample of (120) students girls distributed on three stages . She applied the emotional freedom scale which the researcher has prepared includes (33) items as first form & (30) items as final form & got the psychometric characteristics of it , it is lasted (10) minutes . The researcher used the follow statistical methods , T test of one sample , T test of two independent samples , Pearson’s correlation coefficient , Alpha cronbach , ANOVAs , & Sheffee . In the light of the results she reached to some recommendations & suggestions